Dynamic Analysis Of Ultimate State For Bridges With Multiple Restrainers - Desy Setyowulan (Rekayasa Sipil, 2016)
This paper presents the dynamic analysis of ultimate state for simply-supported bridges with multiple restrainers. Two types of restrainers were installed in bridge, including of restrainer Type 1 and Type 2 which were assembled between adjacent decks and between decks to column, respectively. The effectiveness of multiple unseating prevention devices in simply supported bridges were examined in numerically by using the Vector Form Intrinsic Finite Element (VFIFE). Ground motion recorded during 1999 Taiwan Chi-Chi Earthquake was selected in order to investigate the seismic behavior of the target bridges. According to the numerical results, it was found that installation of restrainer type 1 independently has a better result in protecting the deck of bridges from unseating and column failure.